Vaccination Against SARS-Cov-2 among Patients with Parkinson’s Disease Based on the Results of COVPARK-LT Study - Kaladytė Lokominienė, R.; Lokominaitė, G. (Neurologijos seminarai, 2024)
Background. COVID-19 in patients with Parkinson’s disease leads to worsening of symptoms and development of severe/critical conditions; its long-term consequences are still being investigated. Data on vaccination against SARS-Cov-2 in Parkinson’s disease are inconsistent. There are no publications on this topic regarding Lithuania. Materials and methods. The retrospective study COVPARK-LT was performed in the Vilnius University Hospital Santaros Clinics in 2022. Methods: analysis of anonymous data from electronic patient histories obtained during consultations for Parkinson’s disease in the out-patient department (form E025). Objective: To investigate COVID-19 vaccination status and associated factors in patients with Parkinson’s disease.Results. 173 patients were enrolled, 68 males (39.3%) and 105 females (60.7%), the average age of the cohort was 67.99±1.34 years, the duration of Parkinson’s disease was 7.73±0.54 years. The rate of vaccination against SARS-Cov-2 with at least one dose was 85.6% among study patients and 69.8% in the general population. The rate of full vaccination against SARS-Cov-2 was 81.5% in COVPARK-LT and 33.4% in the general population. The rate of laboratory-proven COVID-19 was 20% (N=5) in the non-vaccinated group of the cohort and 22.3% (N=33) in the vaccinated group (p=0.087). COVID-19 vaccine-negativity was associated with the history of vaccination against non-SARS-Cov-2 infections (odds ratio, OR: 0.18, p < 0.01), vaccination against influenza (OR: 0.21, p
Keywords: Parkinson’s disease; COVID-19; SARS-CoV-2; vaccination